2000
DOI: 10.1086/301499
|View full text |Cite
|
Sign up to set email alerts
|

Proper Motion of the Large Magellanic Cloud using [CLC]QSOs[/CLC] as an Inertial Reference System

Abstract: The proper motion of the Large Magellanic Cloud (LMC) relative to three background quasi-stellar objects has been determined using 125 CCD frames taken from 1989.0 to 1997.2 at the Cassegrain focus of the CTIO 1.5 m telescope. The observation and reduction methods are fully described. The results are compared with those obtained by other authors who use di †erent methods and reference systems for the proper motions. This comparison results in a good agreement for and a rather large discrepancy k a cos d for Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 12 publications
(9 reference statements)
1
29
0
Order By: Relevance
“…It is also worth noting that, if we fix the mass of the Galaxy equal to our most likely mass estimate, there is insufficient matter present to gravitationally bind the LMC, if we adopt the recent proper-motion measurement by Anguita et al (2000). These authors reported rather high proper motions, (µ α cos δ, µ δ ) = (+1.7 ± 0.2, +2.9 ± 0.2), compared to previous measurements, (µ α cos δ, µ δ ) = (+1.94 ± 0.29, −0.14 ± 0.36) (Kroupa & Bastian 1997).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…It is also worth noting that, if we fix the mass of the Galaxy equal to our most likely mass estimate, there is insufficient matter present to gravitationally bind the LMC, if we adopt the recent proper-motion measurement by Anguita et al (2000). These authors reported rather high proper motions, (µ α cos δ, µ δ ) = (+1.7 ± 0.2, +2.9 ± 0.2), compared to previous measurements, (µ α cos δ, µ δ ) = (+1.94 ± 0.29, −0.14 ± 0.36) (Kroupa & Bastian 1997).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…In addition, two QSOs used by Anguita et al (2000) and one by Pedreros et al (2002) to study the proper motion of the LMC are attributed to a private communication by Maza in 1989 and/or do not appear in previous studies. More recently, 1 QSO was confirmed by Hony et al (2011) and 145 QSOs by Kozłowski et al (2012), the latter identified from OGLE-III light-curves.…”
Section: Appendix A: Known Qsos Behind the Magellanic Systemmentioning
confidence: 99%
“…In alphabetical order, the list now contains Draco (Scholtz & Irwin 1993), Canis Major (Dinescu et al 2005b), Carina (Piatek et al 2003), Fornax (Piatek et al 2002;Dinescu et al 2004), the LMC (Jones et al 1994;Kroupa et al 1994;Kroupa & Bastian 1997;Anguita et al 2000;Drake et al 2001;Pedreros et al 2002;Kallivayalil et al 2006b), M33 ( Brunthaler et al 2005), Sagittarius ( Dinescu et al 2005a), Sculptor (Schweitzer et al 1995;Piatek et al 2006), the SMC (Irwin et al 1996;Kallivayalil et al 2006a), and Ursa Minor (Scholtz & Irwin 1993;Schweitzer et al 1997;Piatek et al 2005). This sample is becoming large enough to reveal the three-dimensional nature of motions in the Local Group.…”
Section: Introductionmentioning
confidence: 99%